Insights from the global education survey on the use of VR-haptics in dental education - Bencharit, Sompop; Quinn, Barry; Sittoni-Pino, Maria F.; Arias-Herrera, Santiago; Schick, Simona-Georgiana; Rampf, Sarah; Byrne, Samantha; Shazib, Muhammad A.; Örtengren, Ulf; Lam, Walter Yu Hang; Liukkonen, Mikko; Rice, David; et al. (Frontiers in Dental Medicine, 2025)
BackgroundHaptics-enhanced virtual reality (VR-haptics), a supplementary tool for traditional oral health training, shows promise in enhancing knowledge acquisition, manual dexterity, performance, and student well-being.AimThe aim of this study was to understand dental educators' perceptions and needs regarding the acceptability and application of VR-haptics in dental education, as well as to gather suggestions for system improvements.MethodsIn this global cross-sectional study, the VR-Haptic Thinkers Consortium used a 28-item online questionnaire distributed to 1,023 participants by August 1, 2024. The survey included questions on general demographics, multiple choice and five-point Likert-style questions, and open-ended questions.ResultsA total of 378 responses were collected from 156 institutions. 57% of respondents had a dental doctorate degree and 59% had a PhD. VR-haptic trainers were used more often in preclinical training (94% of responses) than clinical training (46%). The three most common course types with VR-haptics incorporation were restorative, prosthodontic, and endodontic courses. Most respondents thought that the best approach to implementing VR-haptics is alongside phantom head training in the preclinical stage (58%). A third of the feedback on the challenges in VR-haptics utilization in dental training highlighted a need for further hardware and software development, while more than one-fourth cited economic issues in system acquisition and housing, and another one-fourth reported low acceptance of the technology among educators and students. The most mentioned enhancement requests for dental trainers were more diverse training scenarios (20%), improved software (19%) and hardware (19%) elements, and advancements in AI-based personalized training and monitoring (18%). Additionally, 10% of respondents suggested gamification features.ConclusionsVR-haptic technology is constantly evolving and will likely become more and more accepted as an integral part of dental hand skill development to complement traditional preclinical training. Future research and development should emphasize transitioning from preclinical to clinical restorative, prosthodontic, endodontic, and implantology procedures as part of individualized education and patient care.